2022
DOI: 10.1186/s12889-022-13865-8
|View full text |Cite
|
Sign up to set email alerts
|

“I did whatever they wanted me to do”: a qualitative secondary analysis using reproductive justice to explore sexual violence among justice-involved Latina mothers

Abstract: Background One in three women experience sexual violence during their lifetime; however, little is known about this phenomenon with respect to justice-involved Latina mothers. Using the reproductive justice framework as a theoretical lens, we examined sexual violence in Latina mothers who had experienced incarceration and were thus involved in the justice system. Methods This was a secondary analysis of a qualitative data set. The reproductive just… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The reviewed studies revealed the limitation and gaps in research related to giving a reproductive choice among justice-involved Black women. This review mirrors prior literature on limited reproductive autonomy of justice-involved women (Crawford et al, 2022a;Hayes et al, 2020;Sufrin et al, 2015) and, most recently, the Supreme Court's decision over eliminating abortion health care in certain regions of the United States (Dickman et al, 2021). Powerful barriers associated with incarceration sometimes deter or prevent women from accessing emergency contraception, abortion services, or preventive health care of their choice, which can impede their reproductive autonomy (Crawford et al, 2022a;Karlsson & Zeilinski, 2020).…”
Section: Tenet 1: a Call For Reproductive Choicementioning
confidence: 64%
See 1 more Smart Citation
“…The reviewed studies revealed the limitation and gaps in research related to giving a reproductive choice among justice-involved Black women. This review mirrors prior literature on limited reproductive autonomy of justice-involved women (Crawford et al, 2022a;Hayes et al, 2020;Sufrin et al, 2015) and, most recently, the Supreme Court's decision over eliminating abortion health care in certain regions of the United States (Dickman et al, 2021). Powerful barriers associated with incarceration sometimes deter or prevent women from accessing emergency contraception, abortion services, or preventive health care of their choice, which can impede their reproductive autonomy (Crawford et al, 2022a;Karlsson & Zeilinski, 2020).…”
Section: Tenet 1: a Call For Reproductive Choicementioning
confidence: 64%
“…Powerful barriers associated with incarceration sometimes deter or prevent women from accessing emergency contraception, abortion services, or preventive health care of their choice, which can impede their reproductive autonomy (Crawford et al, 2022a; Karlsson & Zeilinski, 2020). Forcing women to continue with unplanned or unwanted pregnancies often result in these women having to engage in sex work or selling illicit substances to financially support themselves and their babies, further inducing trauma, violence, and instances of rearrest, thus further limiting reproductive autonomy (Crawford et al, 2022a; Karlsson & Zeilinski, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the RJ tenets, outcomes from our research indicate the need for multilevel, innovative strategies focused on respectfully and inclusively engaging participants and community partners, promoting equitable collaboration in local communities, encouraging the autonomous right to self-determination, and mitigating power imbalances. Others who successfully used the RJ framework to guide research affirmed our strategies (Crawford, 2021; Crawford, McGlothen-Bell, & Cleveland, 2022; Crawford, McGlothen-Bell, Recto, et al, 2022; Julian et al, 2021; Norwood et al, 2022; Shlafer et al, 2019). Julian et al (2021) and Norwood et al (2022) assert that using RJ to guide research—specifically through participatory approaches—creates an opportunity to empower the community as experts in their lived experience.…”
Section: Discussionmentioning
confidence: 87%
“…Responsible and timely dissemination of results indicates transparency and accountability and creates an environment of co-learning between academia, the public, and those with lived experience (Mosavel et al, 2019). Therefore, in the year after data analysis, findings were disseminated to community partners, data collection sites, and participants who provided consent for follow-up contact at the study conclusion, and discussions regarding the meaning of the study findings and future implications were conducted (Crawford, McGlothen-Bell, & Cleveland, 2022; Crawford, McGlothen-Bell, Recto, et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation